Tradition and Modernisation in Islamic Studies in Pakistan: Continuity and Transformation - Sami Ul Haq, Sami Ul Haq; Ris’an Rusli, Ris’an Rusli; Ismail, Ismail (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2026)
Islamic studies in Pakistan have developed through a complex interaction between classical Islamic scholarly traditions and processes of educational modernisation shaped by the state and modern higher education systems. As a country founded upon an Islamic identity, Pakistan positions Islamic studies in a strategic role, both in the formation of religious discourse and in the construction of national identity. This article aims to analyse the dynamics of tradition and modernisation in Islamic studies in Pakistan by highlighting institutional, epistemological, and curricular continuity and transformation. The study employs a qualitative method based on library research, utilising historical and sociological approaches to examine the development of Islamic education in both madrasas and universities. The findings indicate that modernisation has not replaced traditional Islamic studies; rather, it has facilitated the emergence of hybrid models that integrate classical Islamic sciences with modern academic approaches. This transformation occurs through ongoing negotiations between the scholarly authority of the ulama and the academic demands of universities, and is further shaped by state policies and Pakistan’s socio-political context. The article concludes that Islamic studies in Pakistan represent a sustained dialectical process between tradition and modernity, producing both intellectual continuity and methodological renewal in contemporary Islamic scholarship.